Supporting multilingual learners: Parental roles in modern Islamic boarding school - Wardani, Oktarina Puspita; Turahmat, Turahmat; Afandi, Muhamad; Wahyuningrum, Dwi Wara; Nirmala, Arini Febiantika (Universitas Islam Sultan Agung, 2025)
Bilingual and multilingual education programmes are being adopted with increasing frequency by modern Islamic boarding schools (pesantren) in Indonesia, with the aim of enhancing students’ linguistic abilities and academic performance. This study examines parental involvement in children’s education at multilingual pesantren, with a focus on their roles in supporting language learning and adapting to school language policies. A mixed-methods approach was used to collect data from twenty-five parents via questionnaires and semi-structured in-depth interviews. Grounded theory analysis was then applied using open, axial, and selective coding to identify key themes. The findings reveal five themes: self-development; parental motivation and pride; optimism for future success; emotional support; and parental participation in school activities. Parents view proficiency in Arabic and English as a religious asset and a strategic skill for global engagement. The study highlights the comprehensive nature of parental involvement in multilingual pesantrens and proposes further research into its long-term impact on students' academic and social outcomes.